2008
DOI: 10.1111/j.1365-2966.2008.12951.x
|View full text |Cite
|
Sign up to set email alerts
|

C, N, O abundances in the most metal-poor damped Lyman alpha systems

Abstract: This study focuses on some of the most metal-poor damped Lyα (DLA) absorbers known in the spectra of high-redshift QSOs, using new and archival observations obtained with ultravioletsensitive echelle spectrographs on the Keck and VLT telescopes. The weakness and simple velocity structure of the absorption lines in these systems allow us to measure the abundances of several elements, and in particular those of C, N and O, a group that is difficult to study in DLAs of more typical metallicities. We find that whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
231
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(275 citation statements)
references
References 65 publications
41
231
1
1
Order By: Relevance
“…We also note that the [N/O] ratio is well-determined in this DLA, since both N I and O I trace the H I bearing gas due to charge transfer reactions (Field & Steigman 1971;Steigman et al 1971). Our value of [N/O] is consistent with, or slightly lower than, the primary N/ O plateau (Izotov & Thuan 1999;Centurión et al 2003;van Zee & Haynes 2006;Petitjean et al 2008;Pettini et al 2008;Pettini & Cooke 2012b;Zafar et al 2014).…”
Section: Analysis Methodssupporting
confidence: 73%
“…We also note that the [N/O] ratio is well-determined in this DLA, since both N I and O I trace the H I bearing gas due to charge transfer reactions (Field & Steigman 1971;Steigman et al 1971). Our value of [N/O] is consistent with, or slightly lower than, the primary N/ O plateau (Izotov & Thuan 1999;Centurión et al 2003;van Zee & Haynes 2006;Petitjean et al 2008;Pettini et al 2008;Pettini & Cooke 2012b;Zafar et al 2014).…”
Section: Analysis Methodssupporting
confidence: 73%
“…7, for two different choices of S H , together with those for higher-metallicity disc stars obtained by Bensby & Feltzing (2006) We have included in Fig. 7 the [C/O] measurements in metalpoor DLAs by Pettini et al (2008) which seem to match well the values deduced here in halo stars of similar [O/H]. The good agreement in the [C/O] ratios measured in different astrophysical environments and at different epochs strengthens the interpretation that carbon was somehow overproduced in early stages of galactic chemical evolution.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Erni et al (2006) found the chemical abundances in a DLA with [O/H] ∼ −2.5 to be consistent with enrichment from a single starburst of massive (10−50 M ) zero-metallicity stars. Pettini et al (2008) very recently derived near-solar [C/O] ratios in a small sample of the most metal-poor DLAs/subDLAs known. Becker et al (2006) studied absorption toward high-redshift (4.9 < z < 6.4) quasars, inferring a mean [C/O] ∼ −0.3 in the Lyman alpha forest clouds which trace the low-density and low-metallicity intergalactic medium (IGM).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen can be produced similarly as a primary element, but it can also have a secondary origin in intermediate mass (old) stars generated from the original metals of the star (e.g. Matteucci 1986;Pilyugin et al 2003;Pettini et al 2008). In this simple picture the ratio of N/O is constant if nitrogen has a primary origin, while it depends on O/H if it has a secondary origin.…”
Section: Virial Bh Mass Estimatementioning
confidence: 99%